The genetic puzzle of a SOD1-patient with ocular ptosis and a motor neuron disease: a case report - Vacchiano, Veria; Palombo, Flavia; Ormanbekova, Danara; Fiorini, Claudio; Fiorentino, Alessia; Caporali, Leonardo; Mastrangelo, Andrea; Valentino, Maria Lucia; Capellari, Sabina; Liguori, Rocco; Carelli, Valerio (Frontiers in Genetics, 2023)
Amyotrophic lateral sclerosis (ALS) is a neurodegenerative disease with a complex genetic architecture, showing monogenic, oligogenic, and polygenic inheritance. In this study, we describe the case of a 71 years-old man diagnosed with ALS with atypical clinical features consisting in progressive ocular ptosis and sensorineural deafness. Genetic analyses revealed two heterozygous variants, in the SOD1(OMIM*147450) and the TBK1 (OMIM*604834) genes respectively, and furthermore mitochondrial DNA (mtDNA) sequencing identified the homoplasmic m.14484T>C variant usually associated with Leber's Hereditary Optic Neuropathy (LHON). We discuss how all these variants may synergically impinge on mitochondrial function, possibly contributing to the pathogenic mechanisms which might ultimately lead to the neurodegenerative process, shaping the clinical ALS phenotype enriched by adjunctive clinical features.